Death and memory in early medieval Britain - Williams, Howard (Cambridge University, 2013)
How were the dead remembered in early medieval Britain? This study demonstrates how perceptions of the past and the dead, and hence social identities, were constructed through mortuary practices and commemoration in the period c. AD 400-1100. Drawing on archaeological evidence from across Britain, including the latest archaeological discoveries, Howard Williams presents a new interpretation of the significance of portable artefacts, the body, structures, monuments and landscapes in early medieval mortuary practices. He argues that materials and spaces were used in ritual performances that served as technologies of remembrance, practices that created shared social memories intended to link past, present and future. Through the deployment of material culture, early medieval societies were therefore selectively remembering and forgetting their ancestors and their history. Throwing new light on an important aspect of medieval society, this book is essential reading for all archaeologists and historians with an interest in the early medieval period.